PROSPECTS FOR THE DEVELOPMENT OF MILITARY TOURISM ON THE TERRITORY OF UKRAINE AFTER THE END OF THE RUSSIAN-UKRAINIAN WAR - Barvinok , N. V. (The actual problems of regional economy development, 2022)
The article considers the prospects and importance of military tourism in Ukraine after the Russian-Ukrainian war, which may become one of the important areas of patriotic education of the younger generation of Ukrainians and highlight the scale of the war in the world. The impact of wars and conflicts always has a negative impact on the tourism sector, but the facilities that remain after such events can serve the development of such tourism as military tourism, attracting the attention of both domestic and international tourists. The aim of the article is to study and substantiate military tourism as an important factor in the development of tourism in Ukraine in the postwar period, and to identify the main tourist resources that are the basis for the organization of military tourism. To achieve this goal, the dialectical method of cognition, methods of analysis, synthesis and comparison, system, abstract-logical, modeling method, graphic method and system-structural method were used. The theoretical basis of the study consists of scientific works of domestic and foreign scientists on the development of military tourism and tourism in general and the results of their own research. In the article on the basis of the processed literary sources of foreign and domestic scientists on the structure of military tourism it was found that there is no unified structure, and each author provides his vision of the development of structural elements. Military tourism has been studied, namely, its structural element - military-historical tourism, which is a type of tourism, the purpose of which is to visit places related to military events and facilities created as a result of the war. The main aspects of the development of military tourism after the Russian-Ukrainian war are substantiated and formulated, and it is established that monuments, memorials, museums related to military events should be erected in Ukraine, as well as memorial routes should be created. The priority directions of development of military tourism are offered and the value of development of such kind of tourism for patriotic education of young and adult generation of Ukraine is allocated.